Valsalva retinopathy in pregnancy: an obstetric dilemma - Kaveri, Vismaya; S. K, Manjula; Pawar, Bhargavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Valsalva retinopathy is a unilateral or bilateral condition that occurs when increased intra-thoracic or intra-abdominal pressure transmitted to the eye causes a sharp rise in the intraocular venous pressure, and rupture of superficial retinal capillaries. Pregnancy is known to be a risk factor for Valsalva retinopathy. A 29-year-old G2A1 at 38 weeks of gestation previously normotensive presented with unilateral sudden decrease in vision of 1-day duration. Fundoscopy revealed pre-retinal and vitreous hemorrhage of right eye. A diagnosis of Valsalva retinopathy of pregnancy was made after excluding other probable causes for hemorrhage. She had an elective cesarean section with no further deterioration of vision or recurrence of hemorrhage.